Women leading climate change adaptation: The Gambian experience - Olaniyan, Olawale F.; Baldeh, Demba; Cham, Fafa O.; Morgan, Miranda (2025)
Women leaders play pivotal roles in climate change adaptation in The Gambia, with recent research identifying how women lead efforts that not only contribute to climate resilience but also contribute to food security, economic stability and environmental sustainability. Strengthening women’s leadership is therefore a critical pathway to ensure effective adaptation in the face of climate change.